The Hollywood Jim Crow : The Racial Politics of the Movie Industry - Erigha, Maryann (Book collections on Project MUSE., 2019)
The #OscarsSoWhite campaign, and the content of the leaked Sony emails which revealed, among many other things, that a powerful Hollywood insider didn't believe that Denzel Washington could 'open' a western genre film, provide glaring evidence that the opportunities for people of color in Hollywood are limited. In this work, the author tells the story of inequality, looking at the practices and biases that limit the production and circulation of movies directed by racial minorities. This book examines over 1,300 contemporary films, specifically focusing on directors, to show the key elements at work in maintaining 'the Hollywood Jim Crow'.